Non‐invasive prenatal screening versus prenatal diagnosis by array comparative genomic hybridization: a comparative retrospective study. (23rd May 2017) - Sotiriadis, Alexandros; Papoulidis, Ioannis; Siomou, Elisavet; Papageorgiou, Elena; Eleftheriades, Makarios; Papadopoulos, Vasilios; Alexiou, Maria; Manolakos, Emmanouil; Athanasiadis, Apostolos
Abstract: Objective: To calculate the proportion of array comparative genomic hybridization (aCGH) pathogenic results, that would not be detectable by non‐invasive prenatal screening (NIPS). Methods: This is a comparative study using data from 2779 fetuses, which underwent invasive prenatal diagnosis, and the samples were analyzed using aCGH. The simulated NIPS assay would test for trisomies 21, 18, 13, monosomy X, 47, XXX, 47, XYY, and 47, XXY. Indications for invasive testing were grouped into categories and the absolute, relative rates of pathogenic/likely pathogenic results of aCGH analysis that would not be detectable by NIPS were calculated. Results: The expected rate of aCGH‐detected abnormalities that would not be detectable by NIPS was 28.0% (95% CI 14.3–47.6) for nuchal translucency (NT) 95 to 99th centile; 14.3% (95% 5.0–34.6) for NT > 99th centile; 34.2% (95% CI 21.1–50.1) for high‐risk first‐trimester results (regardless of NT); 52.4% (95% CI 32.4–71.7) for second‐trimester markers; and 50.0% (95% CI 26.8–73.2) for advanced maternal age. The overall rate of aCGH pathogenic/likely pathogenic results was 5.0% and 44.0% (95% CI 36.0–52.2) of them would not be detected by NIPS. Conclusions: Approximately half of the abnormal aCGH results would not be detectable by standard NIPS assays, highlighting the necessity of pre‐test counseling, and illustrating the limitations of NIPS. © 2017 John Wiley & Sons, Ltd. Abstract : What's already known about this topic? Thirty to 45% of clinically significant chromosomal abnormalities, diagnosed after invasive prenatal diagnosis would not be detectable by non‐invasive prenatal screening (NIPS). What does this study add? All invasive samples were examined using aCGH, and NIPS performance was analyzed according to indications for prenatal diagnosis. Approximately 45% of aCGH pathogenic results would not be detectable if NIPS had been the primary test, even for 'soft' indications at first or second trimester.